La part sensible de l'acte - Libois, Joëlle (Le social dans la cité, 2013)
Social educators are involved daily in situations where institutional, profesional and personal elements are intermingled. To understand what is at stake in accompanying young people placed in a shelter, Joëlle Libois explores three profesional situations in order to reach the heart of the activity, enriching them by theoretical contributions (based mainly on Piette, Vygotski, Clot, Mendel). She particularly seeks to maintain coherence between the epistemology of the clinical approach to activity and the methodological building of her approach, and thus grasp the key dimensions of the acting. La part sensible de l'acte focuses on the intention in the action and questions it in the light of the epistemological framing of the analysis of activity, which insists on a dimension that is contextualised and situated in the acting. The activity is understood as an interaction between a manageable part of oneself and of the forces involved that proceed from the resistance opposed by the reality (Clot, 1999), which integrates what the will of the subject cannot grasp. This allows to identify the standardized character of every practice and to insist on the fact that the relational - the notion of presence in reference to the notion of presence-absence (Piette, 2009) and the ability to to let go - is not linked to spontaneous virtues but that it needs being thought over, questioned and practiced in the frame of institutional targets. At last, notions of uncertainty and risk, characteristic to the acting, are opposed to the institutional expectations carried by the normative speeches aiming for social control and evaluation of the action.